2011
DOI: 10.1177/0956797611423547
|View full text |Cite
|
Sign up to set email alerts
|

Group Status Drives Majority and Minority Integration Preferences

Abstract: This research examined preferences for national-and campus-level assimilative and pluralistic policies among Black and White students under different contexts, as majority-and minority-group members. We targeted attitudes at two universities, one where 85% of the student body is White, and another where 76% of students are Black.The results revealed that when a group constituted the majority, its members generally preferred assimilationist policies, and when a group constituted the minority, its members genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 18 publications
6
58
0
2
Order By: Relevance
“…In studying this effect, researchers found that highly identified group members had the largest recognition advantage for ingroup compared to outgroup faces. Moreover, this memory advantage for ingroup members can override racial biases in memory-producing better memory for ingroup members, regardless of their race (Hehman et al, 2012;. These and other studies confirmed that social identities drive face recognition and memory.…”
Section: Face Perceptionsupporting
confidence: 72%
“…In studying this effect, researchers found that highly identified group members had the largest recognition advantage for ingroup compared to outgroup faces. Moreover, this memory advantage for ingroup members can override racial biases in memory-producing better memory for ingroup members, regardless of their race (Hehman et al, 2012;. These and other studies confirmed that social identities drive face recognition and memory.…”
Section: Face Perceptionsupporting
confidence: 72%
“…However, because majority groups tend to prefer a one-group assimilationist model, whereas minorities tend to favor multiculturalism/integration (e.g., Dovidio, et al, 2001;Glasford & Dovidio, 2011;Verkuyten, 2006), we expect that one-group and not dual-identity representation will be the underlying mechanism that accounts for the positive effects of perceived identity and functional indispensability among native Portuguese. That is, we expect that high perceived indispensability of immigrants will trigger the representation that most effectively promotes the majority group's integration goals, that is, assimilationist model (Hehman et al, 2012). This more inclusive one-group representation will then relate to more positive attitudes.…”
Section: Present Researchmentioning
confidence: 96%
“…Specifically, psychological phenomena frequently differ across majority-minority group boundaries (e.g., Hehman et al, 2012), and for racial minorities, negative perceptions of the outgroup (e.g., perceived discrimination by the outgroup) have been shown to buffer against race-based stress (Crocker and Major, 1989;Sellers and Shelton, 2003). On the other hand, research has shown that Blacks who harbor negative attitudes towards Whites are more likely to appraise ambiguous events as discriminatory (Johnson and Lecci, 2003), and perceptions of discrimination are related to heightened anger (Meyer and Baker, 2010) -a strong risk factor for circulatory-related diseases (for a meta-analysis, see Chida and Steptoe, 2009).…”
Section: The Link Between Bias and Ingroup Health For Blacksmentioning
confidence: 99%